Diversity of fliC gene in commensal Escherichia coli derived from various mammals - Baldy-Chudzik, K; Stosik, M (Folia microbiologica, 2007)
Relations between the diversity of the fliC gene conditioning flagellum protein in E. coli and the source of the strain origin are presented. The fliC genes have been identified and characterized in commensal E. coli derived from 10 healthy animal species living in Zoo Safari Park (Poland). The fliC gene was found in 150 strains by the PCR method. The amplifiedfliC products revealed single bands within the range 1.26-2.16 kbp. Forty restriction patterns (classed by restriction analysis with the use of RsaI (PCR-RFLP RsaI; R-types) were determined. The neighbor-joining method was employed to illustrate the distribution of the kinds of R-types. There are 3-8 various R-types of a diversified frequency of occurrence in strains. Application of PCR-RFLP RsaI permitted the identification of alleles of fliC genes characteristic for E. coli and the estimation of their diversity among the animal species. The transmission ways of E. coli fliC+ between organisms of different species were determined and confirmed the role of transmission and horizontal gene transfer in the generation of the allelic diversity of fliC gene in natural E. coli populations.
Keywords: polymorfismus délky restrikčních fragmentů; přenos genů horizontální; Animals; Animals, Zoo; Escherichia coli; Polymorphism, Restriction Fragment Length; zvířata v ZOO; infekce vyvolané Escherichia coli; genetická variace; Escherichia coli Proteins; flagelin; proteiny z Escherichia coli; alely; Flagellin; Escherichia coli Infections; zvířata; fylogeneze; Gene Transfer, Horizontal; savci; Phylogeny; Genetic Variation; Alleles; Mammals